2021
DOI: 10.1186/s12859-021-04437-5
|View full text |Cite
|
Sign up to set email alerts
|

Fast activation maximization for molecular sequence design

Abstract: Background Optimization of DNA and protein sequences based on Machine Learning models is becoming a powerful tool for molecular design. Activation maximization offers a simple design strategy for differentiable models: one-hot coded sequences are first approximated by a continuous representation, which is then iteratively optimized with respect to the predictor oracle by gradient ascent. While elegant, the current version of the method suffers from vanishing gradients and may cause predictor pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 64 publications
(108 reference statements)
0
34
0
Order By: Relevance
“…Since then, graph representations of sequences have become widespread as descriptive tools in bioinformatics, used to reconstruct naturally occurring biological sequences. In modern molecular biology and bioengineering, where the design of synthetic biological systems is fundamentally intertwined with the characterization of natural biological systems, there is growing interest in sequence representations amenable to design tasks (16, 17). However, outside of highly specialized applications (18, 19), graph representations of sequences are far less commonly used in design contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, graph representations of sequences have become widespread as descriptive tools in bioinformatics, used to reconstruct naturally occurring biological sequences. In modern molecular biology and bioengineering, where the design of synthetic biological systems is fundamentally intertwined with the characterization of natural biological systems, there is growing interest in sequence representations amenable to design tasks (16, 17). However, outside of highly specialized applications (18, 19), graph representations of sequences are far less commonly used in design contexts.…”
Section: Discussionmentioning
confidence: 99%
“…The standard solution to this is the Gumbel-Softmax Trick. 15 We used a slightly different approach introduced by Linder and Seelig [13] , which is to simply add a trainable layer normalization that can trainably affect the mean and variance of logits. 66 Recently, Daulton et al [67] showed that BO with probabilistic reparameterization ,like Equation 8, will converge to the true maximum of the acquisition function.…”
Section: B Bayesian Optimizationmentioning
confidence: 99%
“…The standard solution to this is the Gumbel-Softmax Trick. 15 We used a slightly different approach introduced by Linder and Seelig [13] , which is to simply add a trainable layer normalization that can trainably affect the mean and variance of logits. 66 Recently, Daulton et al .…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…BMC Bioinformatics 2021, 22, 510. 2 Fast SeqProp is a computational design algorithm based on activation maximization that can be combined…”
Section: ■ Key Referencesmentioning
confidence: 99%